2015
DOI: 10.1674/0003-0031-173.1.122
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Grassland Biomass Harvest on Nesting Pheasants and Ducks

Abstract: Grasslands enrolled in conservation programs provide important habitat for nesting game birds and waterfowl, but conservation grasslands have been targeted as a source of biomass for bioenergy and this could impact nesting birds. We studied the effects of biomass harvest on nest success and density using 109 blue-winged teal (Anas discors), mallard (Anas platyrhynchos), and ring-necked pheasant (Phasianus colchicus) nests found in southwestern Minnesota during 2009 (pretreatment) and 2010 (posttreatment). Gras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 22 publications
1
0
1
Order By: Relevance
“…Similar to our results, duck nests located near wetlands in western Minnesota were less likely to be successful (Thompson et al 2012). Contrary to our findings, survival was greater for duck nests located closer to wetlands in Minnesota Conservation Reserve Program fields (Jungers et al 2015) but was independent of distance to wetland edge for ducks breeding in Saskatchewan, Canada (Pasitschniak-Arts et al 1998) and North Dakota (Horn et al 2005). We expected that nest concealment might affect nest survival, perhaps because more concealed nests are more difficult to locate by some predators or brood parasites.…”
Section: Effects Of Edge and Nest Concealmentcontrasting
confidence: 99%
“…Similar to our results, duck nests located near wetlands in western Minnesota were less likely to be successful (Thompson et al 2012). Contrary to our findings, survival was greater for duck nests located closer to wetlands in Minnesota Conservation Reserve Program fields (Jungers et al 2015) but was independent of distance to wetland edge for ducks breeding in Saskatchewan, Canada (Pasitschniak-Arts et al 1998) and North Dakota (Horn et al 2005). We expected that nest concealment might affect nest survival, perhaps because more concealed nests are more difficult to locate by some predators or brood parasites.…”
Section: Effects Of Edge and Nest Concealmentcontrasting
confidence: 99%
“…Therefore, the primary advantages of NWSG polycultures over Switchgrass monocultures for biofuel production may be limited to wildlife conservation. Previous studies have observed plant communities among harvest frequencies in conservation grasslands similar to our NWSG plantings (Jungers et al 2015, Stahlheber et al 2016. However, increased cutting frequency can increase light availability, promoting photophilic plant species otherwise deterred by tall vegetation and dense grass canopies (Hautier et al 2009, Wilson andTilman 1991).…”
Section: Discussionsupporting
confidence: 62%